2020
DOI: 10.7554/elife.52176
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the glioblastoma immune microenvironment as basis for the development of new immunotherapeutic strategies

Abstract: Cancer immunotherapy by immune checkpoint blockade has proven its great potential by saving the lives of a proportion of late stage patients with immunogenic tumor types. However, even in these sensitive tumor types, the majority of patients do not sufficiently respond to the therapy. Furthermore, other tumor types, including glioblastoma, remain largely refractory. The glioblastoma immune microenvironment is recognized as highly immunosuppressive, posing a major hurdle for inducing immune-mediated destruction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
162
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(164 citation statements)
references
References 116 publications
1
162
1
Order By: Relevance
“…The resident immune system of the CNS, namely the microglia, are established contributors to CNS malignancies ( 146 ), but there are several other phagocytic myeloid cell populations in the CNS that are also, if not more so, implicated in a poor prognosis of the most aggressive form of CNS malignancy, glioblastoma multiforme (GBM). Perivascular, meningeal, and choroid plexus macrophages of the CNS have generally been overlooked as contributors to GBM ( 147 , 148 ), but the involvement of bone marrow-derived myeloid cells has recently been established, and even positively correlated, to poor outcomes in GBM models ( 116 , 149 ). As seen in the previous cancer studies, GBM TAMs co-express M1- and M2-associated markers, again making simple surface phenotyping of cells rather difficult, and creating the need for mechanism and pathway analysis ( 116 ).…”
Section: Tam/mdsc Identification Across Tumor Typesmentioning
confidence: 99%
See 1 more Smart Citation
“…The resident immune system of the CNS, namely the microglia, are established contributors to CNS malignancies ( 146 ), but there are several other phagocytic myeloid cell populations in the CNS that are also, if not more so, implicated in a poor prognosis of the most aggressive form of CNS malignancy, glioblastoma multiforme (GBM). Perivascular, meningeal, and choroid plexus macrophages of the CNS have generally been overlooked as contributors to GBM ( 147 , 148 ), but the involvement of bone marrow-derived myeloid cells has recently been established, and even positively correlated, to poor outcomes in GBM models ( 116 , 149 ). As seen in the previous cancer studies, GBM TAMs co-express M1- and M2-associated markers, again making simple surface phenotyping of cells rather difficult, and creating the need for mechanism and pathway analysis ( 116 ).…”
Section: Tam/mdsc Identification Across Tumor Typesmentioning
confidence: 99%
“…A cohort of newly diagnosed patients in the study received standard-of-care adjuvant therapy ( 155 ), but the expansion of M-MDSCs were variable, indicating a potential difference in activation of myeloid cells following chemo- or radiotherapy ( 156 , 157 ). Additionally, a number of studies show increased peripheral MDSC counts in subsets of patients who received dexamethasone perioperatively, indicating a potential confounder, or contributor, in correlating overall survival with MDSC levels ( 118 , 148 , 149 ).…”
Section: Tam/mdsc Identification Across Tumor Typesmentioning
confidence: 99%
“…By contrast, recent clinical trials using programed cell death 1 (PD-1) antibodies in recurrent GBM has shown very few responses 2 , even though the ICI seems to reach the brain 3 . Compared to responsive cancers, gliomas harbor a lower burden of somatic mutations, fewer infiltrative T cells and a more immunosuppressive tumor microenvironment (TME) [4][5][6] . These factors could explain why glial tumors remain largely refractory to ICIs.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, recent clinical trials using anti-programmed cell death 1 (PD-1) antibodies in recurrent GBM has shown very few responses [2], even though the ICIs seems to reach the brain [3]. Compared to responsive cancers, gliomas harbor a lower burden of somatic mutations, fewer in ltrative T cells and a more immunosuppressive tumor microenvironment (TME) [4][5][6]. These factors could explain why glial tumors remain largely refractory to ICIs.…”
Section: Introductionmentioning
confidence: 99%